PENINGKATAN PEMASARAN PRODUK UMKM KERAJINAN TANGAN PAPILLON'S SISTERS MELALUI PELATIHAN OPTIMASI MEDIA SOSIAL - Rochman, Fatkhur; Waris S., Abdul; Utomo, Heru; Santoso, Eko Boedhi (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
MSMEs play a strategic role in supporting the national economy, particularly in terms of job creation and income distribution. One of the main challenges faced by MSMEs is product marketing, especially in the current digital era. Therefore, a team of academics involved in community service aims to provide solutions for Papillon's Sisters Craft MSMEs in Malang City through training and mentoring in social media optimization strategies. This SME produces various handicrafts such as bracelets, earrings, necklaces, and other products using quality local and imported materials. However, the use of social media for product marketing has not been maximized. The community service methods employed include knowledge transfer, discussions, and problem-solving sessions, focusing on social media optimization strategies to enhance consumer interaction and boost sales. The results of this initiative indicate an increase in the understanding and ability of the MSMEs to utilize social media, as well as improved online visibility of their products. Social media optimization is expected to be effective in expanding marketing reach and increasing the sales potential of Papillon’s Sisters products.